Wunderlich Syndrome – Minimally Invasive Treatment - Priyadarshee, Piyoosh; Baskar A, Baskar A (Journal of Neonatal Surgery, 2025)
Wunderlich Syndrome (WS), first described in 1856, is a rare, potentially life-threatening condition caused by spontaneous retroperitoneal hemorrhage, often from renal angiomyolipoma (AML). Symptoms include sudden flank pain, a palpable renal mass, and hypotension, making early diagnosis challenging. WS is most commonly caused by benign renal AMLs and malignant renal cell carcinoma. Treatment depends on the underlying cause, hemorrhage severity, and patient’s hemodynamic status, ranging from conservative care to more invasive options like embolization and surgery. This case report discusses a 60-year-old woman who presented with acute right flank pain, pallor, and dizziness. Imaging revealed a large AML in the right kidney with significant hemorrhage. The patient underwent successful emergency renal artery embolization (RAE), which stabilized her condition and stopped the bleeding. Post-procedure imaging confirmed the efficacy of RAE, emphasizing its role in managing WS, offering renal preservation with fewer complications compared to nephrectomy